Animal Models Alternatives: Desideratum during COVID-19 Pandemic - Sharma, Shaweta; Sharma, Akhil; Alam, Aftab; Gupta, Utsav (Indian Journal of Pharmaceutical Education and Research, 2022)
Aim: The present work aimed at the utilization of alternative animal models in research. Background: Animal models from a long time played an important role in drug and vaccine development. However, due to the limitation like logistic, scientific and regulatory the need of alternative animal models became the need of the hour. Materials and Methods: Alternative animal models are strategies which basically substitute the live models. During the COVID-19 ongoing pandemic the fast, safe and effective drug and vaccine development became very crucial. However, due to the animal model limitations, the traditional animal model methods seem to become point of hindrance in the development of COVID-19 drugs and vaccines. Conclusion: Therefore, there is the need of alternative animal models during this pandemic for enhancing the frequency of clearance of clinical trials of corona vaccines. Hence, in the present article the authors briefly discussed about the animal testing, its limitation, various animal models alternatives and their usefulness during COVID-19.
Keywords: In-silico; Non-animal models; Clinical trials; Alternative models; Toxicological; studies